The BH3‐only protein BID impairs the p38‐mediated stress response and promotes hepatocarcinogenesis during chronic liver injury in mice. Issue 3 (1st July 2015) - Orlik, Johanna; Schüngel, Sven; Buitrago‐Molina, Laura Elisa; Marhenke, Silke; Geffers, Robert; Endig, Jessica; Lobschat, Katharina; Rössler, Stephanie; Goeppert, Benjamin; Manns, Michael P.; Gross, Atan; Vogel, Arndt
<x xml:space="preserve">Abstract</x> Apoptosis is critical for maintaining tissue homeostasis, and apoptosis evasion is considered as a hallmark of cancer. However, increasing evidence also suggests that proapoptotic molecules can contribute to the development of cancer, including liver cancer. The aim of this study was to further clarify the role of the proapoptotic B‐cell lymphoma 2 homology domain 3 (BH3)‐only protein BH3 interacting‐domain death agonist (BID) for chronic liver injury (CLI) and hepatocarcinogenesis (HCG). Loss of BID significantly delayed tumor development in two mouse models of Fah‐mediated and HBsTg‐driven HCG, suggesting a tumor‐promoting effect of BID. Liver injury as well as basal and mitogen‐stimulated hepatocyte proliferation were not modulated by BID. Moreover, there was no in vivo or in vitro evidence that BID was involved in DNA damage response in hepatocytes and hepatoma cells. Our data revealed that CLI was associated with strong activation of oxidative stress (OS) response and that BID impaired full activation of p38 after OS. Conclusion: We provide evidence that the tumor‐promoting function of BID in CLI is not related to enhanced proliferation or an impaired DNA damage response. In contrast, BID suppresses p38 activity and facilitates malignant transformation of hepatocytes. (Hepatology 2015;62:816–828)